FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON KEUANGAN DI BEI - IGNATIA MARIA SANIAMISHA; TJHAI FUNG JIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The objective of this research is to obtain empirical evidence of firm size, leverage, corporate strategy, cash holding, profitability, board independence, institutional ownership, and dividend as independent variables to earnings management as dependent variable in Indonesian non-financial companies.This research used companies listed in non-financial sectors in Indonesia Stock Exchange during 2014-2016 as the population. There are 107 companies meet the criteria by using purposive sampling method. The model used in this research is multiple regression analysis.The result show that corporate strategy, cash holding, leverage, and profitability have effect on earnings management, while other independent variables such as firm size, board independence, institutional ownership, and dividend have no effect on earnings management in the company.